2007
DOI: 10.1038/sj.ijo.0803769
|View full text |Cite
|
Sign up to set email alerts
|

Weight maintenance, behaviors and barriers among previous participants of a university-based weight control program

Abstract: Objective: To examine weight loss maintenance among previous participants of a university-based behavioral weight management program and to compare behavioral strategies and perceived barriers between successful and unsuccessful maintainers. Method: Previous program participants (n ¼ 179) completed mailed surveys assessing current weight, weight control behaviors and perceived barriers to weight loss maintenance. Results: At 14.1 ± 10.8 months following completion of treatment, survey respondents were on avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 40 publications
3
47
2
2
Order By: Relevance
“…However, Befort and colleagues [10] have proved that nearly 50% of participants who were 3 years out from their weight-loss phase of treatment maintained a 5% weight loss. They also found that when increased physical activity was included in the lifestylemodification approach, the weight loss was more successfully maintained.…”
Section: Commentsmentioning
confidence: 97%
“…However, Befort and colleagues [10] have proved that nearly 50% of participants who were 3 years out from their weight-loss phase of treatment maintained a 5% weight loss. They also found that when increased physical activity was included in the lifestylemodification approach, the weight loss was more successfully maintained.…”
Section: Commentsmentioning
confidence: 97%
“…Obesity is a risk factor of chronic diseases such as diabetes type 2 and cardiovascular disease [3]. Physical exercise programs have been demonstrated to reduce weight, to support preservation of the reduced weight [4][5][6][7][8], to reduce obesity-related health risks [9], and to improve mental health [10][11][12]. Although physical exercise is beneficial beyond doubt and large physical activity promotion programs have been implemented [13,14], the majority of overweight persons does not engage in sportive activities [15].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the collection of strategies discussed above to weight loss maintenance is supported by the broader descriptive literature (Befort et al, 2008;Elfhag et al, 2005;Gorin et al, 2004;Kayman et al, 1990;Klem et al, 1997;Kruger et al, 2006;Mcguire et al, 1999;Vanderwood et al, 2011;Wadden et al, 2004;Westenhoefer et al, 2004;Wing et al, 2001;Wyatt et al, 2002). Two randomised controlled trials have experimentally investigated whether manipulating the content of an extended contact intervention to focus on strategies related to satisfaction with weight loss outcomes or motivation for weight loss (West et al, 2011) influenced weight loss maintenance.…”
Section: Intervention Strategies Targeting Weight Loss Maintenancementioning
confidence: 97%
“…Self-regulation strategies include self-monitoring, goal setting, planning, self-reward, problem solving, and relapse prevention; all of which have been shown in other studies to be important in weight loss maintenance (Burke et al, 2011;Butryn et al, 2007;Elfhag et al, 2005;Wing et al, 2001). Not only has self-monitoring of weight been shown to be important for weight loss maintenance (as evidenced above), but self-monitoring of physical activity and dietary intake has also been associated with successful weight loss maintenance (Befort et al, 2008;Byrne et al, 2003;Kruger et al, 2006;Vanderwood et al, 2011;Wadden et al, 2004;Wing et al, 2001;Wing et al, 2005). Self-monitoring is thought to impact on maintenance of behaviours because it requires individuals to pay attention to their actions, the conditions under which they occur, and their immediate and long-term effects (Bandura, 1998;Burke et al, 2009).…”
Section: Intervention Strategies Targeting Weight Loss Maintenancementioning
confidence: 99%
See 1 more Smart Citation